Clinical, functional and imaging parallels in the objective status of patients after community-acquired COVID-19-associated pneumonia - L.І. Konopkina; К.V. Rybalka (Civic Union "Communicable Diseases Intensive Care Association", 2024)
OBJECTIVE. To determine the dynamics of clinical symptoms in patients with community-acquired COVID-19-associated pneumonia, imaging and functional examination methods in the early post-acute period of the disease, establishing clinical, functional and imaging parallels in the objective status of patients. MATERIALS AND METHODS. We examined 56 patients after coronavirus disease (COVID-19). The severity of dyspnoea, anamnesis, objective status, pulse oximetry, lung ultrasound (LUS), computed tomography (CT) data, spirometry, body plethysmography, lung diffusion capacity were assessed. Non-parametric methods were used. RESULTS AND DISCUSSION. According to LUS 6 (10.7 %) patients had no pathological changes. Other patients had changes ranging from 3 to 11 points; 24 (48.0 %) had mild interstitial lung lesions, other - moderate. Every second patients showed signs of interstitial inflammation (single, multifocal, confluent B-lines), no more than three segments. Almost all patients (98.0 %) had single A-lines. LUSS was "recruited" mainly due to the LUS-pattern of consolidation (76.0 %) or thickened/ uneven pleura (90.0 %). The area of lung lesions on CT correlated with LUS (r=0.79; p<0.001). CONCLUSIONS. LUS is a highly sensitive method for visualising interstitial changes in the lungs in the post-acute period after COVID-19-associated pneumonia. Most often, there are no impairments in lung ventilation function, but about 20 % of patients require further examination.